Answer:
93
Step-by-step explanation: The first term of AP is -5 and second term means -3.
Common difference(d) = second term - first term
d = (-3)-(-5)
d= 2
Now using the formula of nth T
n
=a
1
+(n−1)d
Here a
1
=−5,n=50,d=2
Puting these values in the formula of of nth term we get
a
n
=−5+(50−1)2
a
n
=−5+98
a
n
=93
Answer:
y = 2x - 5
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
Multiply 13 into (10-6)= 13*4=52. Now find the number sentence that gives 52. This is B because 13*10 - 13*6 = 13*4 the original problem
|a+bi| = √(a² + b²)
-4-√2 i -> take a = -4 and b = -√2
|-4-√2 i| = √[ (-4)² + (<span>-√2)² ]
= </span><span>√[ 16 + 2<span> ]
</span></span><span>= √[ 18 ]</span> = <span>√[ 9 * 2 ]
= 3√2
the absolute value is 3√2</span>
Y is less than or equal to -1